Triagem fitoquímica, atividade antioxidante, alelopática e ação no ciclo celular dos extratos de hortaliças não convencionais - Carvalho, Marcos Schleiden Sousa (2017)
Unconventional vegetables are not a part of a production chain similar to conventional vegetables due to their limited distribution to a certain region. There are many plant families of unconventional vegetables. As an example, there is the Amaranthaceae family, popularly known as Caruru, as considered an invasive plant to crops. In addition to these, there are also the Solanaceae, Tropaeolaceae, Lamiaceae and other non-conventional vegetable families. The objectives of this work were to conduct a phytochemical triage, evaluate the antioxidant potential of unconventional vegetables, and verify the allelopathy action and cellular cycle of the extract obtained from these plants. In the phytochemical triage, conventional tests were conducted to verify the presence of secondary metabolites in the following species: Rumex acetosa L., Tropaeolum majus L., Amaranthus hybridus L., Amaranthus viridis L., Amaranthus pinosus L., Amaranthus deflexus L., Stachys byzantine K. Koch, Solanum muricatum and Solamun betaceum Cav. The allelopathy activity was evaluated using the five Amaranthus species. In the phytochemical triage, the five species of unconventional vegetables presented positive results for tannins, sesquiterpen lactones and other lactones; the tests were positive for azedinha (Rumex acetosa L.) and capuchinha (Tropaeolum majus L.). Negative results were verified for the species of tomate de árvore (Solanum betaceum Cav.) and melãozinho (Solanum muricatum). Regarding the flavonoids, positive results were obtained only for tomate de árvore (Solanum betacum). For the remaining tests, the results were negative. The extracts obtained from A. spinosum, A. viridis, A. deflexus, A. hybridus and A. retroflexus presented positive reactions to organic acid, carotenoids and steroids, as well as polysaccharides, proteins, amino acids, azulenes, depsides, coumarines and saponins. The percentage of antioxidant activity, verified using the ABTS and DPPH free-radical scavenging methods, for the five species studied, increased according to the increase in concentration, thus presenting a dose-dependent effect. By means of the phosphomolybdenum complex method, species T. majus L. and S. byzantine K. Koch presented higher antioxidant activity. Of the five species evaluated, peixinho (S. byzantine K. Koch) presented antioxidant activity for all methods. The synergistic effect of these metabolites presented allelopathy activity for the L. sativa model, with expressive phytotoxicity, acting, especially in the chromosomal bondage with the mitotic spindle, preventing cell division. Species A. spinosum, which presented positive results for all classes of chemical compounds verified in the extracts, was the most promising for future investigation on the possibility of creating a bio-herbicide from compounds isolated from its extract.